Determining the optimal port placement for transoral endoscopic thyroidectomy vestibular approach in a retrospective study - Zhizhou Deng; Xiongqiang Hu; Fangang Zeng; Yujun Guo; Xiaowei Peng (Scientific Reports)
Abstract With the increasing popularity of minimally invasive techniques in thyroid surgery, the transoral endoscopic thyroidectomy vestibular approach (TOETVA) has garnered significant attention. This study aimed to compare the impact of different distances between the observation and operation ports in TOETVA on clinical treatment outcomes. Ninety patients with papillary thyroid carcinoma were retrospectively analyzed. Based on the distance between the observation and operation ports, they were divided into three groups: Group A (2.3–2.7 cm), Group B (less than 2.3 cm), and Group C (more than 2.7 cm). All three groups underwent TOETVA performed by the same surgical team. Operation time, blood loss, postoperative hospital stay, drainage volume, retrieved and metastatic central lymph nodes, postoperative complications, and tumor recurrence were compared among the groups. There were no demographic differences among the three groups. Compared to Groups B and C, patients in Group A had significantly shorter operation times, lower postoperative drainage volumes, and shorter postoperative hospital stays (p < 0.05). There were no significant differences in bleeding amount, retrieved and metastatic central lymph nodes, or incidence of complications among the groups. No postoperative recurrences were observed in any patient. In TOETVA, the best surgical outcomes were achieved when the distance between the observation and operation ports was approximately 2.5 cm (2.3–2.7 cm). This configuration ensures smooth surgical operations and facilitates postoperative rehabilitation, making it worthy of further clinical promotion.